2013
DOI: 10.1002/mrm.24959
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of phase rotation STEAM at 3T: Focus on glutathione

Abstract: Purpose The purpose of this study was to determine the reproducibility of a very short echo time (TE) phase rotation stimulated echo acquisition mode (STEAM) sequence at 3T with a focus on the detection of glutathione. Methods Ten healthy subjects were scanned on two separate visits. Spectra were acquired from voxels placed in the anterior and posterior cingulates. Reproducibility was assessed using mean coefficients of variation (CVs) and mean absolute differences (ADs), and reliability was assessed using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 36 publications
8
60
2
Order By: Relevance
“…Previous efforts demonstrated high scan–rescan reproducibility of the neuroimaging included of the volumetric measurements for subcortical brain structures (Maclaren et al., 2014), cortical gray matter thickness (Dickerson et al., 2008; Han et al., 2006; Li et al., 2015), and diffusion tensor measurements (Acheson et al., 2017; Jovicich et al., 2014). Likewise, several prior studies quantified scan–rescan stability and reproducibility of the MRS measurements at 3T (Wellard, Briellmann, Jennings, & Jackson, 2005; Wijtenburg & Knight‐Scott, 2011; Wijtenburg et al., 2013). Our approach of three scanning sessions and tightly controlled methodological parameters provides for the opportunity to assess these measurements based on the normal physiological variance among them.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts demonstrated high scan–rescan reproducibility of the neuroimaging included of the volumetric measurements for subcortical brain structures (Maclaren et al., 2014), cortical gray matter thickness (Dickerson et al., 2008; Han et al., 2006; Li et al., 2015), and diffusion tensor measurements (Acheson et al., 2017; Jovicich et al., 2014). Likewise, several prior studies quantified scan–rescan stability and reproducibility of the MRS measurements at 3T (Wellard, Briellmann, Jennings, & Jackson, 2005; Wijtenburg & Knight‐Scott, 2011; Wijtenburg et al., 2013). Our approach of three scanning sessions and tightly controlled methodological parameters provides for the opportunity to assess these measurements based on the normal physiological variance among them.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolite levels are reported in institutional units (i.u.). Previously, we have shown that the VTE PR-STEAM method produces excellent reproducibility as determined by a test-retest study (Wijtenburg et al, 2014). There were no significant group differences in the quality of the spectra and metabolite fits.…”
Section: Acc Magnetic Resonance Spectroscopymentioning
confidence: 94%
“…Imaging studies suggest that the medial prefrontal/ACC is a critical component of neural networks that regulates mood and emotionally influenced behavior in depression (Sacher et al, 2012;Phillips et al, 2003) and also a critical region associated with cognitive and emotional impairment in schizophrenia (Fornito et al, 2009;Reid et al, 2010;Carter et al, 2001;Phillips et al, 2003). Spectra were acquired using very short TE (VTE) phase rotation (PR) STEAM sequence: TR/TM/TE = 2000/10/6.5-ms, NEX = 128, 2.5-kHz spectral width, 2048 complex points, and phases: φ1 = 135°, φ2 = 22.5°, φ13 = 112.5°, φADC = 0° ( Wijtenburg and Knight-Scott, 2011;Wijtenburg et al, 2014). A water reference (NEX = 16) was also acquired for phase and eddy current correction as well as quantification.…”
Section: Acc Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…The event-related potential and MRS methods have been described previously, 33,36,52 and details are given in the eMethods in the Supplement. Briefly, the event-related potential was recorded using a 64-channel system 2 (SynAmps; Compumedics Neuroscan) at a 1-kHz sampling rate with bandpass at 0.1 to 200 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…33 Glutamate levels, including the ratio of glutamine to glutamate, were assessed with an MRS technique optimized for the detection of these metabolites. 34-36 The ratio of glutamine to glutamate is thought to reflect glutamatergic neurotransmission whereby the ratio of conversion from glutamine to glutamate may index glutamatergic function. 37 In schizophrenia, a higher ratio of glutamine to glutamate has been found in the cerebrospinal fluid 38 and brain tissue measured with MRS in some studies 39-42 but not in another study.…”
mentioning
confidence: 99%